Anti-migraine medications safety during pregnancy in the US - Bérard, A.; Strom, S.; Albrecht, D.; Kori, S. (Frontiers in Pharmacology, 2024)
Background: Specific antimigraine medications (DHE and triptans) have been associated with adverse pregnancy outcomes in individual studies but lack of consensus remains. Objectives: Quantify the risk of prematurity, low birth weight (LBW), major congenital malformations (MCM), and spontaneous abortions (SA) associated with gestational use of dihydroergotamine (DHE) or triptans in a privately insured cohort of pregnant women in the US. Methods: We conducted a cohort study within the US Merative MarketScan Research Database (2011–2021), composed of a nationally representative sample of patients with employer-provided health insurance. Four independent analyses were conducted to assess the risk of 1) prematurity (<37 weeks of gestation), 2) LBW (birth weight <2,500 g), 3) MCM, and 4) clinically detected SA. Exposure was defined dichotomously as use of DHE or triptan during pregnancy. Generalized estimation equations (GEE) were built to quantify the associations taking into account potential confounders including maternal migraine. Results: Overall, 767,994 pregnant women met eligibility criteria and were included in the analyses on prematurity, LBW, and MCM; 11,121 cases of SA were identified and analyzed. One hundred and eighty-nine (189 (0.02%)) were exposed to DHE (all in the first trimester), and 4,309 (0.56%) to triptans. Adjusting for potential confounders including maternal migraine, DHE was not associated with a statistically significant risk of prematurity (adjusted RR (aRR) 1.17, 95%CI 0.14, 9.74), LBW (aRR 7.76, 95%CI 0.99, 60.83), MCM (aRR 2.27, 95%CI 0.97, 5.29), or SA (aOR 3.19, 95%CI 0.98, 10.38); DHE was associated with an increased risk of septal defects. All estimates were unstable. Similarly, triptan use was not associated with any of the studied outcomes. Discussions and conclusions: After considering maternal migraine and other potential confounders, DHE (first trimester) and triptan exposure during pregnancy were not statistically significantly associated with an increased risk for prematurity, LBW, MCM, or SA. Findings on septal defects could be due to chance, and need replication.